Novosti pri zdravljenju z gensko terapijo - Sedej, Katarina (Zdravniški vestnik, 2014)
Gene therapy is the treatment of genetic disor - ders by introducing genetic material into cells. For this purpose, viral vectors and non-viral methods for introducing genes into cells are used, the later being in general less effective. After the enthusiastic beginings in 1990, gene ther - apy came to a standstill due to side effects of ad - enoviral vectors during gene therapy and when several patients developed leukemia. Nowadays, many studies are testing clinical efficacy of gene therapy to cure cancer, monogenetic disorders and cardiovascular deseases. In last few years we witnessed successful treatments of some patients with severe immune deficiency, Leber's congeni - tal amaurosis, thalassaemia and adrenoleuko - dystrophy. Recently, approval of the first gene therapy by European authorities was reported. It seems that gene therapy, regardless of the rela - tive delay in the 90's, is coming into forefront of advanced therapies.
Keywords: gene therapy; genetske bolezni; genska terapija; inherited genetic disease; therapy; vectors for gene therapy; zdravljenje